Enhanced thermal energy supply via central solar heating plants with seasonal storage: A multi-objective optimization approach. (1st November 2016) - Tulus, Victor; Boer, Dieter; Cabeza, Luisa F.; Jiménez, Laureano; Guillén-Gosálbez, Gonzalo
Graphical abstract: Highlights: A central solar heating plant with seasonal storage (CSHPSS) is examined. A systematic approach for multi-objective optimization of CSHPSS is developed. A TRNSYS simulation is optimized in combination with life cycle analysis principles. The capabilities of the approach are tested through a case study in Barcelona, Spain. Well-designed CSHPSS can bring economic and environmental benefits simultaneously. Abstract: Central solar heating plants with seasonal storage (CSHPSS) are among the most promising technologies to save energy in the industrial and residential-commercial building sectors. This work introduces a systematic approach to optimize these systems according to economic and environmental criteria. Our method, which combines the TRNSYS 17 simulation software with life cycle assessment and multi-objective optimization, identifies optimal CSHPSS designs for any climatic condition and heating demand profile considering economic and environmental criteria simultaneously. The capabilities of this approach are illustrated through its application to a case study of a CSHPSS located in Barcelona (Spain), which satisfies a heating demand for a neighborhood of 1120 dwellings. Numerical results show that the CSHPSS plant leads to significant environmental and economic improvements compared to the use of a conventional natural gas heating system. Our tool can guide engineers and architects in the transition towards a more sustainable residential sector.